2002
DOI: 10.1104/pp.003558
|View full text |Cite
|
Sign up to set email alerts
|

Novel Insight into Vascular, Stress, and Auxin-Dependent and -Independent Gene Expression Programs in Strawberry, a Non-Climacteric Fruit

Abstract: Using cDNA microarrays, a comprehensive investigation of gene expression was carried out in strawberry (Fragaria ϫ ananassa) fruit to understand the flow of events associated with its maturation and non-climacteric ripening. We detected key processes and novel genes not previously associated with fruit development and ripening, related to vascular development, oxidative stress, and auxin response. Microarray analysis during fruit development and in receptacle and seed (achene) tissues established an interestin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
142
0
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 163 publications
(152 citation statements)
references
References 53 publications
9
142
0
1
Order By: Relevance
“…Its sensitivity and reliability has been demonstrated in the study of a variety of phenomena including fruit ripening (Aharoni et al, 2002), the hypersensitive response in response to pathogen (Schenk et al, 2000), and the response to wounding (Cheong et al, 2002). In particular, microarray data was shown to be highly consistent with results obtained by RNA gel multiple times (Desikan et al, 2001;Perez-Amador et al, 2001).…”
mentioning
confidence: 86%
“…Its sensitivity and reliability has been demonstrated in the study of a variety of phenomena including fruit ripening (Aharoni et al, 2002), the hypersensitive response in response to pathogen (Schenk et al, 2000), and the response to wounding (Cheong et al, 2002). In particular, microarray data was shown to be highly consistent with results obtained by RNA gel multiple times (Desikan et al, 2001;Perez-Amador et al, 2001).…”
mentioning
confidence: 86%
“…Observations in both climacteric and nonclimacteric fruits, however, have revealed that decline in auxin levels and in auxin-regulated gene expression correlates with onset of ripening (Given et al 1988;Cohen 1996;Davies et al 1997;Catalá et al 2000), and that ectopically applied auxin delays ripening and represses genes involved in ripening (Vendrell 1985;Manning 1994;Davies et al 1997;Aharoni et al 2002). These results suggest that auxin plays an important role in regulating the onset of fruit ripening in these species, possibly by optimizing the capacity of the fruit to ripen.…”
Section: Fruit Ripeningmentioning
confidence: 99%
“…Elevated levels of caffeic, ferulic, and sinapic acid hexoses might contribute to monolignol biosynthesis and lignin formation in the fruit vasculature (Humphrey and Chapple, 2002;Gross, 2007). Aharoni et al (2002a) provided evidence for the induced expression of genes putatively involved in lignification during ripening in both receptacle and achenes (Aharoni et al, 2002a;BlancoPortales et al, 2002). …”
Section: Metabolism In the Receptacle And Achenes During Mid To Latementioning
confidence: 99%
“…It appears likely that the coordinated action between achene and receptacle is part of the mechanism ensuring achene maturation prior to fruit ripening. In support of this theory, it has been clearly demonstrated that declining auxin levels trigger ripening by inducing the de novo synthesis of several ripening-associated mRNAs (Manning, 1994(Manning, , 1998Aharoni et al, 2002a;Benítez-Burraco et al, 2003;Castillejo et al, 2004). The developmental changes during strawberry maturation are accompanied by massive and coordinated changes in the levels of transcripts related to primary and secondary metabolism (Aharoni and O'Connell, 2002).…”
mentioning
confidence: 93%